Die erste Generation - Pionier:innen der migrationsbezogenen (Sozial-)Pädagogik : Wissenschaftler:innen im Gespräch - Jungk, Sabine, 1959- (Verlag Barbara Budrich, 2021)
In conversation with leading scientists, the "early years" of (social) education in the context of migration are reconstructed, from 1970 to the 1990s: Georg Auernheimer, Ursula Boos-N|nning, Stefan Gaitanides, Franz Hamburger, Leonie Herwartz -Emden, Marianne Kr|ger-Potratz and Wolfgang Nieke report on the development of their research approaches, embedded in biographical, historical-migration-political and practical contexts, as well as on contemporary discourses. In particular, this gives students of educational science and social work a clear access to theoretical and Practical traditions and thus a better understanding of current debates